2014
DOI: 10.1111/jace.13340
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Annealing Atmosphere on the Electrical Properties of MgNb2O6/ITO Heterostructures

Abstract: The effects of annealing atmosphere (N2, air and O2) on the electrical properties of sol–gel‐derived MgNb2O6/ITO heterostructures are discussed in this work. All samples exhibited the amorphous phase and were highly transparent. The percentage of Nb4+ content increased when the films were annealed in the oxygen‐deficient conditions, which could lead to semiconducting films. In addition, the results show that the electrical properties of sol–gel‐derived MgNb2O6 thin films could be tuned based on the annealing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…The characteristic spectra of the 400°C-annealed films (x = 0, 0.2, 0.6, 1) are shown in Figure 4. The binding energy for Mg 2p and Zn 2p revealed divalent oxidation states, which are very similar to those found in our previous work [6,7]. The O 1s and Nb 3d spectra of the films could be decomposed clear shoulders (non-lattice oxygen and Nb 4+ ).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The characteristic spectra of the 400°C-annealed films (x = 0, 0.2, 0.6, 1) are shown in Figure 4. The binding energy for Mg 2p and Zn 2p revealed divalent oxidation states, which are very similar to those found in our previous work [6,7]. The O 1s and Nb 3d spectra of the films could be decomposed clear shoulders (non-lattice oxygen and Nb 4+ ).…”
Section: Resultssupporting
confidence: 87%
“…As the annealing temperature increased to 500°C, clear diffraction peaks identified as columbite-M 2+ Nb 2 O 6 (M = Mg or Zn) phase were observed. Based on the findings of our previous study [6,7], the crystalline temperature of the MNO films is over 600°C. These results indicated that the crystalline temperature of the magnesium-based columbite thin films could be effectively reduced by zinc substitution.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations